Application of It-Based Learning Media to Improve the Basic Skills of Sewing Technology - Mutmainnah, Tri; Munoto, Munoto; Marniati, Marniati; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to determine the activities of students in the basic learning activities of sewing technology using video media, to determine the learning outcomes of basic students of sewing technology using video media, and to determine students' responses to the basic learning activities of sewing technology using video media. This type of research is Classroom Action Research (CAR). The learning method is implemented using the direct learning method. Data collection techniques use observation to get data about student activities, performance tests to determine student learning outcomes, and questionnaires to determine student responses. Data analysis using quantitative descriptive. The results showed that student activities which include preliminary, core, and closing activities were said to be very good with an average value of 93% in the first cycle and rose to 96% in the second cycle. Student learning outcomes reached 73% grade completeness in the first cycle and rose to 82% in the second cycle. The average percentage of success in cycle I and II was 77% in the good category. The results of students' responses stated that they agreed that video media made them have a high willingness to participate in learning by 56%, with 47% of students strongly agree that learning with video media was very interesting and not boring, 58% agreed that it was easier to understand learning materials with video media, and 39% agree that video media motivate students to excel.